Textuality as a linguistic mechanism for codifying legal maxims in Islamic criminal law - Zakariyah, Luqman (Association of Muslim Social Scientists, 2013)
Studying the works of medieval Qur'anic exegetes reveals that they explored approaches to interpreting the Qur'an based on the contextualization of Qur'anic principles and concepts. As this article will show, several of these approaches include the notions textuality, intertextuality, and hypertextuality. This article examines one such approach by focusing on the use of textuality as a linguistic mechanism to complement the juristic methodology of codifying legal maxims (qawa'id fiqhiyah) from Qur'anic exegesis. It explores a number of relevant Qur'anic exegeses and synthesizes how Muslim exegetes view the use of textuality with regard to the development of Islamic legal maxims. This article also notes that legal maxims codified by this approach are potentially subject to exception when applied to Islamic criminal law, although, as this article ultimately explains, the basic rule may be static. I also examine the claim that legal maxims codified directly from the sacred texts are unquestionable. This article concludes that the remit of legal maxims codified from textual revelations be done so directly or indirectly, however,, this does not preclude their actual application from scrutiny.